On the Design of Novel Trident Shaped Triple Wideband Antenna for Wireless 5G Applications - Shinde, Jayashree; Shinde, Pratap (Journal of Scientific Research, 2026)
This paper presents compact design of novel modified trident shaped 5G antenna for triple band operation. The key point of antenna design methodology is to increase the electrical length of antenna by defection in antenna patch in the form of three radiating tooth. The radiating patch tooth allows the excited surface current to flow along its periphery and at its center. This increases the electrical length of the antenna, which decreases lower edge frequency of operating band. The magnetic coupling developed between ground slot of plane and radiating patch generates multiple resonant frequency modes, which are merged to give rise enhanced bandwidth. The rejection filters embedded in the antenna geometry play important role in splitting the fractional wide bandwidth of 150 % into triple band operation by rejecting two frequency band centered at 3.5 GHz and 5.2 GHz. The triple band operation achieved impedance bandwidth of 1.07 GHz (2.39 GHz-3.46 GHz), 1.06 GHz (4.11 GHz-5.17 GHz), and 9.7 GHz (5.30 GHz-15 GHz), exhibiting fractional bandwidth of 36.58 %, 22.84 % and 95.57 % respectively. The antenna exhibits a peak gain of 9.32 dB. The proposed antenna is suitable for 5G applications, covering the sub 6 GHz (n77, n78), sub 7 GHz (n96) bands, and broadband communication.